Experimental Analysis of Vibration Reduction of Boring Bar with Tapered Mass-Rubber Dynamic Vibration Absorber (MR-DVA) - Firsty Azzah Athifah; Wiwiek Hendrowati (Engineering Proceedings, 2025)
One of the machining processes that can be performed on a lathe machine is the boring process, which is used to enlarge holes in a workpiece using a cutting tool called a boring bar. During the boring process, excessive vibration or chatter occurs, which can significantly degrade the surface quality of the workpiece. To reduce these vibrations, a system called the Mass-Rubber Dynamic Vibration Absorber (MR-DVA) is used. A tapered MR-DVA is used, and it is located on the cavity of the customized boring bar. The absorber mass is made of brass, and the absorber stiffness is made of natural rubber. The MR-DVA is designed with various dimension ratios: 10/21, 14/21, and 16/21. The boring bar designed consists of a regular boring bar and a customized boring bar (with MR-DVA) with a diameter of 32 mm and a length-to-diameter (L/D) ratio of 7. The experiment was carried out with variations in cutting parameters such as the cutting speed, feed rate, and depth of cut as well as the variations in the taper ratio of the MR-DVA. The experiment shows that a customized boring bar with a tapered MR-DVA can reduce vibration, and the combination of variation that is optimal to reduce vibration is a customized boring bar with a taper ratio of 14/21. With the obtained optimal parameters for reducing vibrations, the manufacturing efficiency and product quality will be enhanced.